Basic Multiplication Knowledge Acquiring Based on Mathematical of Fingering System - Junaedi, Junaedi; Wahab, Abdul; Arofah, Irvana; Nugroho, Arya Setya; Permana, Erwin Putera (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Acquiring Basic Knowledge Multiplication is one stage of skill trainings. The activities associated with skill development are designed to acclimate students to thinking quickly and precisely about facts, concepts, formulas, and problem-solving techniques. One technique for skill coaching is to employ the Mathematical of Fingering System. These writings are a type of library research in which the author discusses the importance of basic multiplication in the education of Islamic elementary school teachers. Correspondingly, the researchers examine how the concept of the basic multiplication knowledge acquiring based on mathematical of fingering system, and the application of the education of Islamic elementary school teachers are incorporated into the basic multiplication knowledge acquiring based on mathematical of fingering system.